Lactic and propionic acid bacteria starter cultures for improved nutritional properties of pea, faba bean and lentil - Kahala, Minna; Blasco, Lucia; Bragge, Rina; Porcellato, Davide; Østlie, Hilde Marit; Rundberget, Thomas; Baz-Lomba, Jose Antonio; Pihlava, Juha-Matti; Hellström, Jarkko; Gullberg Jørgensen, Emilie; Joutsjoki, Vesa; Gulbrandsen Devold, Tove; et al. (Elsevier, 2024)
Increasing plant-based food consumption as a sustainable and health-oriented alternative to meat is pivotal. Pulses are rich in proteins, minerals, and vitamins; however, they also contain antinutritional compounds, impairing their nutritional value. This study addresses this challenge through the development and application of four distinct microbial consortia in pulse-based fermentations, featuring lactic acid bacteria or a combination of lactic and propionic acid bacteria. Microbial starters significantly reduced galacto-oligosaccharides in all pulse materials, concurrently degrading vicine and convicine in faba beans, while the impact on tannins in faba beans and lentil was moderate. Fermentation with lactic acid and propionic acid bacteria consortia exhibited notable vitamin B12 production, and the effect on the content of phenolic compounds of the studied pulses was also evidenced. Additionally, genomic analyses discerned distinctive profiles among the samples, elucidating the microbial community dynamics shaping fermentation outcomes. The results of this study proved how fermentation can advance the development of pulse-based products with improved nutritional and sustainability attributes.
Keywords: lactic acid bacteria; fermentation (alteration); antinutrient; pulses; vitamin B12